Excess Maternal Weight Gain and Large for Gestational Age Risk among Women with Gestational Diabetes - Berggren, Erica K.; Stuebe, Alison M.; Boggess, Kim A. (American Journal of Perinatology, 2015)
Objective To determine whether, among women with gestational diabetes (GDM), gestational weight gain above Institute of Medicine (IOM) guidelines increases the risk of large for gestational age (LGA) neonates.Study Design We conducted a retrospective cohort study of singleton term pregnancies with GDM delivered at University of North Carolina Women's Hospital, Chapel Hill, NC from January 2002 to May 2010. We used Poisson regression modeling to estimate LGA risk (birth weight > 90th percentile for gestational age), by body mass index class and adherence to 2009 IOM weight gain guidelines. Women meeting IOM guidelines were the referent group. Final adjusted models included race/ethnicity, medical management of GDM, and gestational age at delivery.Results Among the 466 women studied, mean ± standard deviation birth weight was 3,526 ± 544 g; 18% (82/466) delivered LGA neonates. Birth weight was greatest among women exceeding, compared with meeting or gaining less than, IOM guidelines (3,703 ± 545 vs. 3,490 ± 505 vs. 3,328 ± 503, p = 0.001). Exceeding IOM guideline was associated with LGA among obese women (adjusted risk ratio 2.62, 95% confidence interval 1.25, 5.50) but not among overweight or normal weight women.Conclusion Targeting gestational weight gain, a modifiable risk factor, independent of GDM treatment, may decrease LGA risk. Women with GDM may benefit from tailored weight gain recommendations.
Keywords: gestational diabetes; gestational weight gain; large for gestational age; overweight; obesity